2021
DOI: 10.3389/fonc.2020.616440
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Tumor Cells in Resectable Pancreatic Ductal Adenocarcinoma: A Prospective Evaluation as a Prognostic Marker

Abstract: Circulating tumor cells (CTCs) are useful biomarkers of many solid tumors, but are infrequently detected in early stage pancreatic ductal adenocarcinomas (PDACs). The first drainage of pancreatic venous blood flow come to portal vein and pass through the liver, and they finally go out for peripheral blood. We thought that comparing CTCs from portal vein and peripheral blood could enable us to understand the clinical meaning of CTCs from each different site in PDACs. Therefore, we aimed to determine 1) whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…In lieu of traditional tumor tissue biopsy, which is invasive and only provides a static representation of the tumor, liquid biopsies are non-invasive and can present real-time insights throughout the course of disease [ 108 ]. Hence, Song et al evaluated plectin as a marker of circulating tumor cells (CTCs) from portal vein and peripheral blood samples of early-stage PDAC patients [ 109 ]. They were able to identify plectin-positive CTCs in 43.8% and 50% of portal blood and peripheral blood samples, respectively.…”
Section: Clinical Utility Of Plectinmentioning
confidence: 99%
See 2 more Smart Citations
“…In lieu of traditional tumor tissue biopsy, which is invasive and only provides a static representation of the tumor, liquid biopsies are non-invasive and can present real-time insights throughout the course of disease [ 108 ]. Hence, Song et al evaluated plectin as a marker of circulating tumor cells (CTCs) from portal vein and peripheral blood samples of early-stage PDAC patients [ 109 ]. They were able to identify plectin-positive CTCs in 43.8% and 50% of portal blood and peripheral blood samples, respectively.…”
Section: Clinical Utility Of Plectinmentioning
confidence: 99%
“…They were able to identify plectin-positive CTCs in 43.8% and 50% of portal blood and peripheral blood samples, respectively. Moreover, no plectin-positive CTCs were detected in samples from healthy volunteers [ 109 ]. However, the number of plectin-positive CTCs did not relate to disease staging, nor did it show a significant association with overall survival [ 109 ].…”
Section: Clinical Utility Of Plectinmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that healthy subjects had negligible CTC counts (mean, 0 CTCs/7.5 mL; median, 0 CTCs/7.5 mL; range, 0-5 CTCs/7.5mL of blood) when EpCAM and CK antibodies were used to detect CTCs (23, 24). Recently, we have also showed the specificity of Plectin-1 to capture CTCs in PDAC (22). In twenty-eight blood samples (3ml/each) from healthy donors, there was no single positive staining of Plectin-1 for CTCs in 17 samples (61%), and 11 healthy donors (39%) had 0.3∌0.7 CTCs per ml of blood (Mean±SD, 0.16±0.21 CTC/ml; Median 0.00 CTC/ml) ( Supplementary Figure 2 ).…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, Plectin-1 distinguished PDAC from benign inflammatory diseases, like chronic pancreatitis (21). Recently, we have reported that captured PDAC CTCs were confirmed using Plectin-1 detection antibody as well as EpCAM antibody with KRAS mutation (22). Here, we examined whether Plectin-1 combined with EpCAM could improve CTC detection and the Plectin-1 positive PDAC CTCs can be used as prognostic biomarkers.…”
Section: Introductionmentioning
confidence: 99%